Low back pain - Ebnezar, John (India : Jaypee Brothers Medical Publishers, 2012)
This manual covers all types of lower back pain. Beginning with an introduction to low back ache, the text examines uncommon disorders, such as spina bifida, scoliosis and tuberculosis spine, and then common conditions, for example, intervertebral disk prolapse. With nearly 270 images and illustrations, the book also discusses the common causes of lower back pain -- poor posture, sedentary lifestyle; and the uncommon causes such as diseases of the lower spine, or radiating pain from the abdominal and genitourinary organs. Short summaries, clinical photographs, X-rays and anecdotes are provided for easy reference and to help understanding.
SECTION I: INTRODUCTION CHAPTER 1:Introduction To Low Backache SECTION II: UNCOMMON BACKACHE CHAPTER 2:Uncommon Causes For Low Backaches CHAPTER 3:Spina Bifida (Occulta And Manifesta) CHAPTER 4:Ankylosing Spondylitis CHAPTER 5:Scoliosis CHAPTER 6:Osteoporosis CHAPTER 7:Spondylolisthesis CHAPTER 8:Seronegative Spondyloarthropathies CHAPTER 9:Lumbar Spondylosis And Lumbar Canal Stenosis
Incluye contenido
Incluye índice
Keywords: LUMBALGIA; LOW BACK PAIN